Espraiamento urbano e planejamento integrado na Região Metropolitana de Goiânia: análise e cenários - Naciff, Yordana Dias das Neves (2024)
Urban sprawl, characterized by the dispersed and disorderly expansion of cities, results in a series of challenges, such as the creation of urban voids, decreased population density, sociospatial segregation, and increased dependence on automobiles. These effects contribute to the formation of disconnected and difficult-to-manage regions, complicating integrated urban planning among the municipalities of the metropolitan area. Using the Metropolitan Region of Goiânia (RMG) as a case study, this thesis analyzes the impacts of urban sprawl on population and socio-territorial dynamics, economic factors, urban mobility, and environmental aspects. A systemic methodological procedure was proposed, based on General Systems Theory and the use of georeferencing tools, which allows for the analysis of interactions between various urban systems. The Dinamica EGO software was used to simulate urban expansion scenarios for the studied territory, aiming to develop territorial planning guidelines. The objective of this thesis is to identify and analyze the impacts of urban sprawl on the urban dynamics of the Metropolitan Region of Goiânia, with the goal of establishing guidelines and actions for integrated urban development in the RMG. To this, the thesis is divided into two parts, “defining the scene” and “ordering the scene”. The developed method validates the hypothesis constructed for this study and can be applied to other metropolitan regions using different urban variables. Among the contributions of this research are the application of General Systems Theory for urban analysis and the development of future urban expansion scenarios for the RMG. The results obtained underscore the importance of an integrated and systemic approach to mitigating urban sprawl, aiming to improve the quality of life in metropolitan regions and ensuring integrated urban development that is both socially just and environmentally sustainable.